Efektivitas Model Pembelajaran Kooperatif Dalam Meningkatkan Hasil Belajar Siswa - Mandopa, Andi Saputra Mandopa; alwendi; Lela Budiarti; Puspita, Nurkhasanah Rina (JURNAL TECHLINK, 2025)
This study aims to determine the effectiveness of the implementation of cooperative learning models in improving student learning outcomes in certain subjects. This study uses a quantitative method with an experimental design of One-Group Pretest-Posttest Design, where one group of students is given treatment in the form of a cooperative learning model without a control group. The research instrument is a learning outcome test carried out before (pre-test) and after (post-test) the implementation model. The data collected were analyzed using statistical tests to determine the difference in pre-test and post-test scores. The results showed a significant increase in student learning outcomes, with an average pre-test score of 69 and increasing to 89.33 in the post-test after the implementation of the cooperative learning model. This increase indicates that the cooperative learning model not only improves students' understanding of the material, but also increases students' active involvement in the learning process, encourages social interaction, and develops cooperation skills between students. Based on the results of the analysis, it can be concluded that the cooperative learning model is effective in improving student learning outcomes and is feasible to be applied in the learning process in schools. Based on these results, it can be concluded that the cooperative learning model is effective in improving student learning outcomes.